INFORMATION SYSTEM FOR WORK EXIT PERMIT AT CIAMIS STATE COURT - winda, melisa; Septiana, Yosep; Apriyani, Yanti; Kusmira, Mira (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
ABSTRACT- The District Court is a judicial institution within the General Court environment domiciled in the regency or city capital. Submitting information for permits to enter and leave work manually is considered less effective in terms of controlling employee activities, especially going work obligations during working hours for personal or other interests. with the submission method only giving reports verbally to Sub Personnel and Ortala, without any written submissions/reports that must be known by the head of the Agency to apply the SOP that applies to the Agency Observations are made by visiting and observing directly to the research site to see the ongoing process The interview was conducted with one of the employees of the Ciamis district court. Interviews were conducted by asking several questions to determine the system running there. This literature study is used as reference material in doing this final project. Literature studies are used by searching for material through books, the Internet, and journals related to this research. We are designing an information system for entering and leaving work permits (sikasja) to streamline activities in the work environment. So that research results can be utilized by agencies as a primary reference for solving existing problems. As a step of adaptation and use of technology in the current era of digitalization. Knowing the job role of each position in Class 1B agencies, Keywords: Court, System, Waterfall, Personnel, Letters